2012
DOI: 10.1155/2012/847686
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Epileptic Seizure from Scalp EEG Using Lyapunov Spectrum

Abstract: One of the inherent weaknesses of the EEG signal processing is noises and artifacts. To overcome it, some methods for prediction of epilepsy recently reported in the literature are based on the evaluation of chaotic behavior of intracranial electroencephalographic (EEG) recordings. These methods reduced noises, but they were hazardous to patients. In this study, we propose using Lyapunov spectrum to filter noise and detect epilepsy on scalp EEG signals only. We determined that the Lyapunov spectrum can be cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…A positive value of λ max is indicative of chaos in the system. The Rosenstein algorithm was chosen because it is fast, easy to implement, efficient for short time series, and robust to changes parameters (Khoa et al., 2012). Positive λ max values also indicate a short‐term prediction horizon in the system.…”
Section: Methodsmentioning
confidence: 99%
“…A positive value of λ max is indicative of chaos in the system. The Rosenstein algorithm was chosen because it is fast, easy to implement, efficient for short time series, and robust to changes parameters (Khoa et al., 2012). Positive λ max values also indicate a short‐term prediction horizon in the system.…”
Section: Methodsmentioning
confidence: 99%
“…Babloyantz and Destexhe concluded using Lyapunov exponents that a healthy brain is more chaotic than an epileptic brain, and there is variability loss in the brain's electrical activity during an epileptic seizure (43). The diagnostic values of the Lyapunov exponent have also been found to be similar to a diagnosis from medical doctors in the case of typical general epilepsy (27). In another study, the Lyapunov exponent was found to be decreased for epileptic subjects compared with normal subjects (26).…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies have indicated that nonlinear methods could be valuable to understand neuronal dynamics. In one study, an epileptic seizure was detected from EEG signals using nonlinear time series analysis techniques (26) as well as independent component analysis (27).…”
Section: Introductionmentioning
confidence: 99%
“…The most common variant is the storiform pleomorphic type, which comprises spindle cells in a storiform pattern, plump histiocyte-like cells and pleomorphic multinucleated giant cells [ 6 , 7 ]. The prognosis of MFH is generally poor [ 8 ]. Definitive treatment is surgical, either with wide local excision or total resection.…”
Section: Discussionmentioning
confidence: 99%